Acid mine drainage treatment using zero-valent iron nanoparticles in biochemical passive reactors. Issue 13 (7th June 2022) - Vásquez, Yaneth; Galvis, José A.; Pazos, Jhon; Vera, Camila; Herrera, Oscar
ABSTRACT: Acid mine drainage (AMD) is the major effluent generated from metal and coal mines, causing serious ecological risks and degradation of aquatic habitats and surrounding soil quality. Biochemical passive reactors (BPRs) are an option for improving AMD affected water. This study investigates the effect of the size and concentration of zerovalent iron nanoparticles (nZVI) on the efficiency of batch BPRs during AMD remediation. Atomic force microscopy (AFM) and transmission electron microscopy (TEM) were also used as complementary techniques for the investigation of the changes in microbial cells and nZVI properties after the AMD remediation. The results from the batch experiment showed that the concentration of nZVI increases the pH and decreases ORP during AMD treatment, thus favouring the removal of metals. The results also suggest that metal sulfide precipitation occurred in all the batch with reactive mixture but was greater in reactors amended with nZVI of larger size. This study revealed that the presence of nZVI in the BPR leads to metal removal as well as the inhibition of sulfate-reducing bacteria (SRB) activity. Microscopy study indicated that the addition of nZVI creates a morphological change on certain microorganisms in which the cellular membrane was fully covered with nZVI, inducing cell lysis process. These results show that nZVI is a promising reactive material for the treatment of AMD in BPR systems. GRAPHICAL ABSTRACT: UF0001